If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + x + -3x = 2 Combine like terms: x + -3x = -2x 2 + -2x = 2 Add '-2' to each side of the equation. 2 + -2 + -2x = 2 + -2 Combine like terms: 2 + -2 = 0 0 + -2x = 2 + -2 -2x = 2 + -2 Combine like terms: 2 + -2 = 0 -2x = 0 Solving -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-2'. x = 0 Simplifying x = 0
| 14(v+2)-2v=3(4v+1)-11 | | 2(f+4)=18 | | 2,7x0,5x4/5 | | 34=6x+3x+7 | | 9=2s+5 | | 3t^4=-t^2+2 | | 2(j-15)-1=3 | | pq+4opx+qy+z=0 | | 64=2x+7x+1 | | 6x+3-x=-22 | | 20x^2-32x+12=0 | | 114=6x+3x+6 | | 31.25=w/5 | | -9k=-10k+6 | | 4f=3+f | | v=4/3X3.14X10X2 | | -9s+8=-10s | | 4x-3x+7=12x-6-9 | | 1/6c=12 | | 4x+4=5x+6 | | x^2-4x+4=10 | | 7m^3-80m^2+100m=0 | | -4+3j=2j | | 15+0.17x=40 | | 35=2y+9 | | 21xy-7x= | | -9/10b=-18 | | x+250y=1000 | | y+6.2=-2.4 | | (2x-6)(x-1)=0 | | (-10-5x)-1=14 | | -(4a-3b+5c)= |